Orsaker till kolik hos häst - Edstam, Linnea (2015)
The aim of this work was to investigate possible risk factors for colic in horses, and to describe what horse owners can do to prevent this condition. The gastrointestinal system of the horse is constructed for continuous high fibre consumption for a period up to eighteen hours a day. Under those conditions, the continuous flow of digesta stimulates gut motility so that the intestines move constantly. When the diet is changed rapidly and the horse is being fed high rations of concentrates each day, the risk of getting colic is higher compared to when consuming less concentrates and giving the horse a stable diet. Lack or absence of access to water and restricted allowance to move freely every day increases the risk of colic. Changed management practices and decreased activity contributes to increased risks, as well as other critical risk factors such as breed, season and age combined with rapidly changed management. More knowledge and education is required of the horse owners about feed requirements in the horse, management routines and rapidly changed activity.